2017
DOI: 10.1371/journal.ppat.1006461
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus superantigen SElX is a bifunctional toxin that inhibits neutrophil function

Abstract: Bacterial superantigens (SAgs) cause Vβ-dependent T-cell proliferation leading to immune dysregulation associated with the pathogenesis of life-threatening infections such as toxic shock syndrome, and necrotizing pneumonia. Previously, we demonstrated that staphylococcal enterotoxin-like toxin X (SElX) from Staphylococcus aureus is a classical superantigen that exhibits T-cell activation in a Vβ-specific manner, and contributes to the pathogenesis of necrotizing pneumonia. Here, we discovered that SElX can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 62 publications
0
37
0
1
Order By: Relevance
“…In addition to TSS, staphylococcal SAgs have been strongly associated with a number of other diseases including life-threatening conditions such as pneumonia and endocarditis [ 3 ]. SAgs in severe S. aureus- mediated pneumonia are likely to over activate the immune system, induce damage to the pulmonary epithelium, and subvert neutrophil activation resulting in serve inflammatory pathology [ 3 , 74 , 75 ]. Specifically, SEB, SEC, SElX and TSST-1 have all been shown to contribute to mortality in a rabbit model of necrotizing pneumonia [ 38 , 74 , 75 ].…”
Section: Staphylococcal Superantigens and Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to TSS, staphylococcal SAgs have been strongly associated with a number of other diseases including life-threatening conditions such as pneumonia and endocarditis [ 3 ]. SAgs in severe S. aureus- mediated pneumonia are likely to over activate the immune system, induce damage to the pulmonary epithelium, and subvert neutrophil activation resulting in serve inflammatory pathology [ 3 , 74 , 75 ]. Specifically, SEB, SEC, SElX and TSST-1 have all been shown to contribute to mortality in a rabbit model of necrotizing pneumonia [ 38 , 74 , 75 ].…”
Section: Staphylococcal Superantigens and Diseasementioning
confidence: 99%
“…SAgs in severe S. aureus- mediated pneumonia are likely to over activate the immune system, induce damage to the pulmonary epithelium, and subvert neutrophil activation resulting in serve inflammatory pathology [ 3 , 74 , 75 ]. Specifically, SEB, SEC, SElX and TSST-1 have all been shown to contribute to mortality in a rabbit model of necrotizing pneumonia [ 38 , 74 , 75 ]. Rabbit models of S. aureus infection have also demonstrated that SAgs can contribute to the disease process in the development of infective endocarditis, augmenting the formation and persistence of microbial heart valve vegetations [ 55 , 76 ].…”
Section: Staphylococcal Superantigens and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These toxins are preferentially directed against immune cells to induce inflammation and cell death. With respect to superantigens, different models have demonstrated enhanced activation and cytotoxicity against the immune system that contributes to lung infection [32,33]. The efficient bacterial defense against immune cells is of particular importance during lung infection, as immune cells are abundantly recruited to lung tissue during infection and the interaction of S. aureus with the immune system appears to be a key factor in the pathogenesis of pneumonia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was discovered that SE l X has a unique sialic acid-binding motif. This motif allows SE l X to interact with adhesion molecules on neutrophils involved in immune recognition and cell activation (Langley et al, 2017 ; Tuffs et al, 2017 ). Importantly, the ability of SE l X to bind neutrophils, which are considered the first line of defense against S. aureus (Spaan et al, 2013 ), was crucial for disease progression in a rabbit model of necrotizing pneumonia.…”
Section: The Enterotoxins Are Immunomodulators Of Multiple Immune Celmentioning
confidence: 99%